If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7(-1x + 4) = -2(x + -5) + 6x Reorder the terms: 3x + 7(4 + -1x) = -2(x + -5) + 6x 3x + (4 * 7 + -1x * 7) = -2(x + -5) + 6x 3x + (28 + -7x) = -2(x + -5) + 6x Reorder the terms: 28 + 3x + -7x = -2(x + -5) + 6x Combine like terms: 3x + -7x = -4x 28 + -4x = -2(x + -5) + 6x Reorder the terms: 28 + -4x = -2(-5 + x) + 6x 28 + -4x = (-5 * -2 + x * -2) + 6x 28 + -4x = (10 + -2x) + 6x Combine like terms: -2x + 6x = 4x 28 + -4x = 10 + 4x Solving 28 + -4x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 28 + -4x + -4x = 10 + 4x + -4x Combine like terms: -4x + -4x = -8x 28 + -8x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 28 + -8x = 10 + 0 28 + -8x = 10 Add '-28' to each side of the equation. 28 + -28 + -8x = 10 + -28 Combine like terms: 28 + -28 = 0 0 + -8x = 10 + -28 -8x = 10 + -28 Combine like terms: 10 + -28 = -18 -8x = -18 Divide each side by '-8'. x = 2.25 Simplifying x = 2.25
| 5-2(2n-8)=-3(2n-5) | | -2=-3+m/8 | | 5x-25y=5 | | 78=6-6v | | -6+a/2=-8 | | 6(x+3)=6+8(x-1) | | X^2-x+0.05=0 | | 22+x+2=90 | | 4n+18=34whatisn | | (3a^2b)(-ab^2)= | | x/31=-20 | | 54=12x-(4x+10) | | 8(r-11)=3r | | 5x^2-18x+10=0 | | -36x=2772 | | 5x-7=-37 | | 7(x-3)+5=19 | | (-4x^3y^2z)(4x^5y^4z^3)= | | -10=x/2 | | 7(x-3)=-4x+78 | | 11=x/10 | | 16=2x+8 | | 9n^2+12n+4=36 | | 11(n-6)=100n | | 29-8k+16k= | | -15=12-3x | | 1/7x-1/2x=-1/14 | | -5+2x=7 | | 5u-4=6 | | 4(m+4)=60 | | 8x+1+15x+10=360 | | 8x+1+15x+10=180 |